Co-Infection in HIV positive patients with retinitis: A case series of dual positive intraocular fluid polymerase chain reaction - Hayes, Morgan (Division of Ophthalmology, 2021)
Objective To report 10 cases of dual-positive intraocular fluid PCR results in infectious retinitis where both pathogens may be clinically relevant. Methods A retrospective observational case series including 10 patients with infectious retinitis who demonstrated more than 1 positive result on PCR testing over a 10-year period at a single referral centre. Results Of 619 patients who underwent intraocular fluid PCR testing for infectious retinitis, we identified 10 patients (1.62%) where 2 organisms were isolated. All 10 patients were HIV positive with profound immunosuppression (mean CD4 count 67cells/mm3) and extensive retinitis. CMV was identified in all 10 cases whilst the additional pathogen was VZV in 6 cases, Toxoplasma gondii in 3 cases and HSV in 1 case. Conclusions PCR analysis of ocular fluids is important in this clinical scenario since more than one pathogen may be present and clinically relevant. Clinicians should be aware of this rare phenomenon to ensure that, when it does occur, consideration be given to adjusting treatment to cover both organisms.